Overcommitment as a predictor of effort–reward imbalance: evidence from an 8-year follow-up study - Feldt, Taru; Hyvönen, Katriina; Mäkikangas, Anne; Rantanen, Jorma; Huhtala, Mari; Kinnunen, Ulla (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVE ': 'The effort–reward imbalance (ERI) model includes the personal characteristic of overcommitment (OC) and the job-related characteristics of effort, reward, and ERI, all of which are assumed to play a role in an employee’s health and well-being at work. The aim of the present longitudinal study was to shed more light on the dynamics of the ERI model by investigating the basic hypotheses related to the role of OC in the model, ie, to establish whether an employee’s OC could be a risk factor for an increased experience of high effort, low reward, and high ERI at work. ' ' METHODS ': 'The study was based on 5-wave, 8-year follow-up data collected among Finnish professionals in 2006 (T1, N=747), 2008 (T2, N=422), 2010 (T3, N=368), 2012 (T4, N=325), and 2014 (T5, N=273). The participants were mostly male (85% at T1) and the majority of them worked in technical fields. OC, effort, reward, and ERI were measured at each time point with the 23-item ERI scale. ' ' RESULTS ': 'Three cross-lagged structural equation models (SEM) were estimated and compared by using full information maximum likelihood method: (i) OC predicted later experiences of effort, reward, and ERI (normal causation model), (ii) effort, reward, and ERI predicted later OC (reversed causation model), and (iii) associations in normal causal and reversed causal models were simultaneously valid (reciprocal causation model). The results supported the normal causation model: strong OC predicted later experiences of high effort, low reward and high ERI. ' ' CONCLUSIONS ': 'High OC is a risk factor for an increased experience of job strain factors; that is, high effort, low reward, and high ERI. Thus, OC is a risk factor not only for an employee’s well-being and health but also for an increasing risk for perceiving adverse job strain factors in the working environment.
Keywords: cross-lagged analysis; effort–reward imbalance; effort–reward imbalance model; ERI; ERI model; follow-up study; job strain; overcommitment; predictor